Europe and Central Asia - Meeting the Environment Millennium Development Goal - World Bank (Washington, DC, 2013)
This report reviews the status of the 28 countries of Europe and Central Asia (ECA) with respect to the environmental Millennium Development Goal (MDG). The aim of this goal is to 'ensure environmental sustainability,' which is elaborated by a set of three targets and eight indicators. The indicators for the environment MDG are important not only as measures of environmental sustainability, but also as contributors to the health and poverty goals. In ECA, these linkages are clearly brought out for the water supply and sanitation indicators, but also apply to the carbon reduction, forestry and biodiversity indicators. The three targets and its indicator are: (i) halve, by 2015, the proportion of people without sustainable access to safe drinking water and basic sanitation: (a) proportion of population with sustainable access to an improved water source; and (b) proportion of population with access to basic sanitation; (ii) integrate the principles of sustainable development into country policies and programs and reverse the losses of environmental resources: (a) energy use (kg oil equivalent) per $1 GDP(Purchasing Power Parity(PPP)); (b) carbon dioxide emissions (per capita); (c) proportion of land area covered by forest; (d) ratio of area protected to maintain biological diversity to surface area; and (e) proportion of population using solid fuels; (iii) by 2020 to have achieved a significant improvement in the lives of at least 100 million slum dwellers: (a) proportion of households with access to secure tenure.